Lexical semantic analysis to support ontology maintenance modelling of failure-mode-effect analysis. (22nd June 2022) - Ebrahimipour, Vahid; Sheikhalishahi, Mohammad
This paper proposes an event-based ontology approach for supporting a failure-mode-effect analysis (FMEA), based on a lexical semantic analysis. The approach constructs a straightforward lexical semantic for analysing the semantic and syntactic features of the contextual structures of maintenance reports to facilitate translation and interpretation for knowledge reasoning in the format of FMEA. The knowledge is converted into a computer-understandable representation with less heterogeneity and ambiguity. At first, it maps the argument structure into a causal event structure, in which an event is represented as a group of highly frequent contextual features or words logically linked together to shape structured arguments. Then, Valin's model is employed in the format of [Event-State-Activity-Accomplishment-Result] to determine the syntax-sematic interface and linking rules in the causal chain. Finally, the metadata and/or hypernyms of causal events are represented, to accommodate ontology modelling for semantic extraction and cause-effect interpretation using Web Ontology Language (W3C).